2008
DOI: 10.1248/bpb.31.266
|View full text |Cite
|
Sign up to set email alerts
|

Formulations for Protecting the Probiotic Saccharomyces boulardii from Degradation in Acidic Condition

Abstract: Saccharomyces boulardii is a nonpathogenic yeast with proven health benefits, some of them depending on its viability. However, the living yeast is sensitive to environmental conditions and its viability is less than 1% in the faeces after oral administration. Therefore, we assessed the survival conditions of S. boulardii in aqueous suspension and in its freeze-dried form and we formulated microspheres with the former and tablets with the latter in order to preserve the viability of the probiotic. While the vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 36 publications
(53 reference statements)
0
15
0
Order By: Relevance
“…Lyophilized products are stable at room temperature, have the advantage of portability and maintain high viability counts over prolonged periods (Graff et al, 2008 Therefore, the mechanisms of this yeast's probiotic action need to be identified, and any potential for virulence must be fully investigated.…”
Section: S Boulardiimentioning
confidence: 99%
“…Lyophilized products are stable at room temperature, have the advantage of portability and maintain high viability counts over prolonged periods (Graff et al, 2008 Therefore, the mechanisms of this yeast's probiotic action need to be identified, and any potential for virulence must be fully investigated.…”
Section: S Boulardiimentioning
confidence: 99%
“…1991). This low survival rate is attributed to killing of S. boulardii cells during their transit through the gastro‐intestinal tract, especially in the stomach (Graff et al. 2008a,b).…”
Section: Introductionmentioning
confidence: 99%
“…can survive extreme physiological conditions such as stomach acidity, bile salt and partially simulated gastro intestinal tract conditions as compare to sensitive strains of Lactobacillus and Bifidobacterium. In addition, they are stable in different manufacturing methods as well as storage and shipping conditions [11,12].…”
mentioning
confidence: 99%